Effect of sterilization methods on the absorption capacity of absorbent paper points - Carlos Menezes Aguiar; Thaísa Torres; Daniela Mendes; Bruna Farias; Andréa Cruz Câmara (Brazilian Dental Science)
The purpose of the present study was to analyze the influence of sterilization methods on the absorption capacity of different brands of standardized absorbent paper points, testing the hypothesis that there is a positive correlation between the percentage of increased absorption capacity and sterilization method. Standardized endodontic absorbent paper points (size rank from #15 to #40) from three different brands of three manufacturers were used for this study (Dentsply, Endopoints, Tanari). Twenty absorbent paper points of each size were used. The initial weight (iw) of each absorbent paper point was recorded using a digital scale. After sterilization, the dry weight (dw) of each absorbent paper point was determined. Each paper point was then introduced into a 2% methylene blue solution during 20 seconds until complete saturation. The paper points were removed from the solution and the wet weight (ww) was determined, with absorption capacity calculated from a difference between ww-dw. Data was statistically analyzed using Tukey’s test and the Student’s t-test (p<0.05). Tanari paper points exhibited the best absorption capacity among the brands analyzed, but the difference was non-significant. Sterilization process did not influence the absorption capacity of absorbent paper points.